Hubungan Antara Pola Makan Dan Status Gizi Dengan Tingkat Kebugaran Atlet Dayung - Rhildan Rahman Muharam (Journal of Sport Science and Education, 2019)
The purpose of this study is to obtain a broader picture of the relationship between diet and nutritional status with the level of physical fitness of rowing athletes in western district regency. The method used by quantitative descriptive method, the participants involved in this research are rowing athletes of west bandung regency, X1 dietary food diet 2x24 hours, X2 nutritional status calculation of body mass index (imt) and Y level of cooper test, with correlation and test contribution using regression test. The results of the first hypothesis test shows the value of X1 counts of 0.174> (0.05) (10). The result of the second hypothesis X2 test shows the value of 0.603> (0.05) (10), it can be concluded there is no significant relationship between diet and nutritional status with physical fitness level athletes paddle west bandung regency. Based on the results of regression analysis X1 contribution X2 & Y obtained value R = 0.476, with R square value of 0.227 it can be concluded that Ho accepted. This shows there is no significant relationship between diet and nutritional status with fitness level. While the value of R square addressed the percentage of values that consider the effect of X to Y of 22.7%, while the rest of 73.3% influenced by other factors. Can be concluded there is no relationship between diet and nutritional status with the level of physical fitness athletes rowing district west bandung